+0

# A plus b equals 1. A squared plus b squared is 2. What is a cubed plus b cubed

0
287
2

A plus b equals 1. A squared plus b squared is 2. What is a cubed plus b cubed

Guest Nov 24, 2014

#1
+81007
+13

A + b = 1  →  b = 1 - A

So, subsituting, we have

A2 + (1 - A)2 = 2

A2 + 1 - 2A  + A2 = 2    rearrange

2a2 - 2A - 1 = 0      And using the on-site solver and substituting "x" for "A" ......we have....

$${\mathtt{2}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{2}}}{\mathtt{\,-\,}}{\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{1}} = {\mathtt{0}} \Rightarrow \left\{ \begin{array}{l}{\mathtt{x}} = {\mathtt{\,-\,}}{\frac{\left({\sqrt{{\mathtt{3}}}}{\mathtt{\,-\,}}{\mathtt{1}}\right)}{{\mathtt{2}}}}\\ {\mathtt{x}} = {\frac{\left({\sqrt{{\mathtt{3}}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)}{{\mathtt{2}}}}\\ \end{array} \right\} \Rightarrow \left\{ \begin{array}{l}{\mathtt{x}} = -{\mathtt{0.366\: \!025\: \!403\: \!784\: \!438\: \!6}}\\ {\mathtt{x}} = {\mathtt{1.366\: \!025\: \!403\: \!784\: \!438\: \!6}}\\ \end{array} \right\}$$

So, b = 1 - (-[√3 - 1 ] /  2)   =  [1 + √3 ] / 2     or  b = 1 - [ [1 + √3 ] / 2] = [1 - √3 ] / 2

So

A3 + b3 = ( [1 - √3] / 2 )3  + ( [1 + √3 ] / 2)3 = ( [1 + √3] / 2 )3  + ( [1 - √3 ] / 2)3 = 2.5

CPhill  Nov 24, 2014
Sort:

#1
+81007
+13

A + b = 1  →  b = 1 - A

So, subsituting, we have

A2 + (1 - A)2 = 2

A2 + 1 - 2A  + A2 = 2    rearrange

2a2 - 2A - 1 = 0      And using the on-site solver and substituting "x" for "A" ......we have....

$${\mathtt{2}}{\mathtt{\,\times\,}}{{\mathtt{x}}}^{{\mathtt{2}}}{\mathtt{\,-\,}}{\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{1}} = {\mathtt{0}} \Rightarrow \left\{ \begin{array}{l}{\mathtt{x}} = {\mathtt{\,-\,}}{\frac{\left({\sqrt{{\mathtt{3}}}}{\mathtt{\,-\,}}{\mathtt{1}}\right)}{{\mathtt{2}}}}\\ {\mathtt{x}} = {\frac{\left({\sqrt{{\mathtt{3}}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)}{{\mathtt{2}}}}\\ \end{array} \right\} \Rightarrow \left\{ \begin{array}{l}{\mathtt{x}} = -{\mathtt{0.366\: \!025\: \!403\: \!784\: \!438\: \!6}}\\ {\mathtt{x}} = {\mathtt{1.366\: \!025\: \!403\: \!784\: \!438\: \!6}}\\ \end{array} \right\}$$

So, b = 1 - (-[√3 - 1 ] /  2)   =  [1 + √3 ] / 2     or  b = 1 - [ [1 + √3 ] / 2] = [1 - √3 ] / 2

So

A3 + b3 = ( [1 - √3] / 2 )3  + ( [1 + √3 ] / 2)3 = ( [1 + √3] / 2 )3  + ( [1 - √3 ] / 2)3 = 2.5

CPhill  Nov 24, 2014
#2
+18829
+10

A plus b equals 1. A squared plus b squared is 2. What is a cubed plus b cubed

$$a+b=1 \\ a^2+b^2 = 2\\ a^3+b^3 = ?$$

I.

$$a^3+b^3 = (a+b)(a^2-ab+b^2) \quad | \quad a+b=1 \ and \ a^2 +b^2 = 2 \\ a^3+b^3 = 1*(2-ab) \\ a^3 + b^3 = 2 -ab$$

II.

$$(a+b)^2 = a^2+ 2ab + b^2 \quad | \quad a+b=1 \ and \ a^2+b^2 = 2\\ 1^2 = 2 + 2ab \\ -1 = 2ab \\ ab = -\frac{1}{2}$$

III.

$$a^3+b^3 = 2-ab \quad | \quad ab = -\frac{1}{2} \\ a^3+b^3 = 2 - ( -\frac{1}{2} ) \\ a^3+b^3 = 2 + \frac{1}{2} \\ \boxed{a^3+b^3 = 2.5}$$

heureka  Nov 24, 2014

### 14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details